Highlights in bioorganic chemistry: methods and applications - Schmuck, Carsten; Wennemers, Helga (Wiley-VCH, 2004)
This is a fascinating introduction to the topic. Spanning the spectrum of nucleic acid chemistry, carbohydrates, peptides, molecular recognition, biosynthesis and natural biosynthesis, right up to medical and biophysical chemistry, the book provides advanced students and those already working in the field with a balanced overview. In more than 30 contributions, a new generation of recognized scientists gives an account of the latest research in such areas as * Artificial receptors for the stabilization of ß-sheet structures * Carbohydrate recognition by artificial receptors * Combinatorial chemistry as a tool for the discovery of catalysts * The interaction of NO and peroxynitrite with hemoglobin and myoglobin * Inhibitors against human mast-cell-tryptase as a potential approach to conquering asthma * The selectivity of DNA replication. A readily accessible survey for everyone wishing to stay abreast of developments. With a Foreword by Ronald Breslow.